Changes in CREB and deltaFosB are associated with the behavioural sensitization induced by methylenedioxypyrovalerone. (July 2016) - Buenrostro-Jáuregui, Mario; Ciudad-Roberts, Andres; Moreno, Josep; Muñoz-Villegas, Patricia; López-Arnau, Raúl; Pubill, David; Escubedo, Elena; Camarasa, Jorge
Methylenedioxypyrovalerone (MDPV) is a synthetic cathinone which has recently emerged as a designer drug of abuse. The objective of this study was to investigate the locomotor sensitization induced by MDPV in adolescent mice, and associated neuroplastic changes in the nucleus accumbens and striatum through deltaFosB and CREB expression. Behavioural testing consisted of three phases: Phase I: conditioning regimen with MDPV (0.3 mg/kg/day for five days) or saline; Phase II: resting (11 days); Phase III: challenged with MDPV (0.3 mg/kg), cocaine (10 mg/kg) or saline on day 16 for both groups. Mice repeatedly exposed to MDPV increased locomotor activity by 165–200% following acute MDPV or cocaine administration after an 11-day resting period, showing a MDPV-induced sensitization to itself and to cocaine. An explanation for this phenomenon could be the common mechanism of action between these two psychostimulants. Furthermore, the MDPV challenge resulted in higher levels of phospho-CREB in MDPV-conditioned mice compared with MDPV-naive mice, probably due to an up-regulation of the cAMP pathway. Likewise, MDPV exposure induced a persistent increase in the striatal expression of deltaFosB; the priming dose of MDPV also produced a significant increase in the accumbal expression of this transcription factor. This study constitutes the first evidence that an exposure to a low dose of MDPV during adolescence induces behavioural sensitization and provides a neurobiological basis for a relationship between MDPV and cocaine. We hypothesize that, similar to cocaine, both CREB and deltaFosB play a role in the induction of this behavioural sensitization.